2021
DOI: 10.1016/j.parepi.2021.e00203
|View full text |Cite
|
Sign up to set email alerts
|

Liver and kidney dysfunction, hypoglycemia, and thrombocytopenia in Plasmodium vivax malaria patients at a Colombian Northwest region

Abstract: Plasmodium vivax has high morbidity, it is the Plasmodium species with the greatest worldwide distribution, and its ability to trigger severe symptoms is currently recognized. The present study aims to compare the clinical and epidemiological characteristics of patients with P. vivax malaria, with and without complication criteria, in an endemic area for malaria transmission in northwest Colombia. A descriptive cross-sectional study was carried out betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…The patients in the study did not present cerebral malaria or pulmonary alterations. The clinical and epidemiological characteristics of this cohort were previously described [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients in the study did not present cerebral malaria or pulmonary alterations. The clinical and epidemiological characteristics of this cohort were previously described [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the group of patients with severe malaria, the main findings are illustrated in Fig 1 . The patients in the study did not present cerebral malaria or pulmonary alterations. The clinical and epidemiological characteristics of this cohort were previously described [26].…”
Section: Clinical Characteristics Of P Vivax Malaria Patientsmentioning
confidence: 99%
“…The higher the parasitaemia in the host, the higher the consumption of glucose that may lead to hypoglycaemia, mainly in severe malaria. Hypoglycaemia may provoke dizziness, palpitations, tremors and loss of consciousness [ 51 ]. Careful glucose monitoring should be targeted in these complications, especially in those patients with G6PD deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The main findings showed that a cohort of 142 individuals with confirmed P. falciparum , 61 with P. vivax , four with P. malariae and 37 with P. ovale infection provided the mean of platelets and standard deviation (SD) (106.4 ± 72.66) (×10 9 /L), (101.0 ± 58.69) (×10 9 /L), (82.5 ± 28.34) (×10 9 /L) and (107.9 ± 54.25) (×10 9 /L), respectively. Null hypothesis value (74.2 × 10 9 /L) was available in the literature [ 24–26 ]. To attain a 95% confidence interval with a two-sided type I error of 5% and a statistical power of 80%, 42 participants for P. falciparum , 40 for P. vivax , 94 for P. malariae and 23 for P. ovale were required, respectively.…”
Section: Methodsmentioning
confidence: 99%